2009
DOI: 10.1158/0008-5472.can-08-1363
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MCAM/CD146 as the Target Antigen of a Human Monoclonal Antibody that Recognizes Both Epithelioid and Sarcomatoid Types of Mesothelioma

Abstract: The prognosis for patients diagnosed with mesothelioma is generally poor, and currently available treatments are usually ineffective. Therapies that specifically target tumor cells hold much promise for the treatment of cancers that are resistant to current approaches. We have previously selected phage antibody display libraries on mesothelioma cell lines to identify a panel of internalizing human single chain (scFv) antibodies that target mesothelioma-associated, clinically represented cell surface antigens a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 38 publications
3
61
0
4
Order By: Relevance
“…2 and 7) were CD146 positive by OJ79. These results show that CD146 is a marker capable of discriminating between malignant pleural mesothelioma and reactive mesothelium, in agreement with the recent findings by Bidlingmaier et al 27 that CD146 has been detected in mesothelioma with high frequency but not in one case of normal mesothelium using tissue microarrays.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…2 and 7) were CD146 positive by OJ79. These results show that CD146 is a marker capable of discriminating between malignant pleural mesothelioma and reactive mesothelium, in agreement with the recent findings by Bidlingmaier et al 27 that CD146 has been detected in mesothelioma with high frequency but not in one case of normal mesothelium using tissue microarrays.…”
Section: Discussionsupporting
confidence: 93%
“…Bidlingmaier et al 27 have recently identified CD146 as the surface antigen recognized by the targeting single-chain antibody that was capable of internalizing epitopes on the plasma membrane of mesothelioma cells. Using a mesothelioma xenograft model, the single-chain antibody against CD146 was shown to possess the potential for targeting therapy of mesothelioma.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous reports have shown that CD146 significantly correlates with advanced tumor stage in malignant melanoma (13), prostate cancer (14), epithelial ovarian cancer (15), and mesothelioma (27,28), little is known about the underlying mechanisms. Here, we report a unique role for CD146; the induction of EMTs to promote breast cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…80,83 Initial exploration of the possibility of using CD146, a cell adhesion molecule, as a diagnostic marker for distinguishing MM from reactive mesothelial proliferation started a couple years ago, and few studies have been published. 84,85 One study performed by Sato et al 84 evaluated the expression of 2 clones of CD146 (OJ79 and EPR3208) in 23 pleural MMs and 28 reactive mesothelial proliferation cases. They found that the sensitivities of OJ79 and EPR3208 were 94% and 90%, respectively, and the …”
Section: Application Of Ihc For Distinguishing MM From Reactive Mesotmentioning
confidence: 99%